2019
DOI: 10.1210/jc.2019-00035
|View full text |Cite
|
Sign up to set email alerts
|

Poor Glycemic Control Is Associated With Impaired Bone Accrual in the Year Following a Diagnosis of Type 1 Diabetes

Abstract: Context Type 1 diabetes (T1D) is associated with an increased fracture risk across the life course. The effects on bone accrual early in the disease are unknown. Objective To characterize changes in bone density and structure over the year following diagnosis of T1D and to identify contributors to impaired bone accrual. Design Prospective cohort study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 43 publications
2
17
0
2
Order By: Relevance
“…Hence, changes may occur early in T1D as children with T1D have decreased fn BMD with a Z-score of −0.57, similar to previously described meta-analysis 13,18,19. In addition, children with T1D and glycated hemoglobin A1c (HbA1c) ≥7.5% have lower bone mass accrual during twelve months18 and adolescents with T1D and HbA1c ≥8.0% have lower total body BMD compared to those with better glycemic control 20. The early onset of low BMD in T1D may be due to calcium loss, as 25% of young women with T1D had greater urinary calcium excretion and less calcium retention in a study that used a dual stable calcium isotope to evaluate calcium intake and excretion 21.…”
Section: Bone Mineral Density In Type 1 Diabetessupporting
confidence: 78%
See 1 more Smart Citation
“…Hence, changes may occur early in T1D as children with T1D have decreased fn BMD with a Z-score of −0.57, similar to previously described meta-analysis 13,18,19. In addition, children with T1D and glycated hemoglobin A1c (HbA1c) ≥7.5% have lower bone mass accrual during twelve months18 and adolescents with T1D and HbA1c ≥8.0% have lower total body BMD compared to those with better glycemic control 20. The early onset of low BMD in T1D may be due to calcium loss, as 25% of young women with T1D had greater urinary calcium excretion and less calcium retention in a study that used a dual stable calcium isotope to evaluate calcium intake and excretion 21.…”
Section: Bone Mineral Density In Type 1 Diabetessupporting
confidence: 78%
“…Likewise, Hamilton et al followed 48 patients with T1D for 10 years and found that BMD at the spine, fn, and forearm remained stable when adjusted for body mass index (BMI) 17. Hence, changes may occur early in T1D as children with T1D have decreased fn BMD with a Z-score of −0.57, similar to previously described meta-analysis 13,18,19. In addition, children with T1D and glycated hemoglobin A1c (HbA1c) ≥7.5% have lower bone mass accrual during twelve months18 and adolescents with T1D and HbA1c ≥8.0% have lower total body BMD compared to those with better glycemic control 20.…”
Section: Bone Mineral Density In Type 1 Diabetesmentioning
confidence: 53%
“…Both the lack of insulin, among other pancreatic anabolic hormones, and low IGF1 levels suppress the terminal differentiation of mesenchymal stem cells (MSCs) into osteoblasts in addition to osteoblastic activity [11]. Therefore, this inhibits skeletal growth at a young age, which leads to an inadequate accrual of peak bone mass [12,13,14,15,16]. On the contrary, T2DM affects bone health in advanced stages of the disease where many factors such as insulinopenia, hyperglycemia, the development of advanced glycation end products (AGEs), chronic inflammation, and microvascular disease coincide to negatively affect bone architecture and biomechanical properties of the bone (Figure 1) [17,18].…”
Section: Bone Mineral Densitymentioning
confidence: 99%
“…Although strict glycemic control does not necessarily reduce the risk of fractures, several studies have indicated that poor glycemic control (HbA1c ≥8%–9%) increases fracture risk compared with standard control in T1D and T2D, and that bone accrual following the diagnosis of T1D was impaired in individuals with poor glycemic control . Thus, for patients with diabetes, glycemic control remains a top priority, and the decrease in blood glucose level should be smooth to prevent hypoglycemia and its consequences, including fracture …”
Section: Comprehensive Management Of Fracture Risk In Diabetesmentioning
confidence: 99%